1999
DOI: 10.1039/a807418f
|View full text |Cite
|
Sign up to set email alerts
|

Cationic zirconocene complexes with benzyl and Si(SiMe3)3 substituted cyclopentadienyl ligands

Abstract: Alkyl zirconocenes [Zr(η-C 5 H 4 R) 2 X 2 ] (where R = CH 2 Ph, X = Cl 1a or Me 1b; R = CHPh 2 , X = Cl 2a or Me 2b; R = Si(SiMe 3 ) 3 , X = Cl 4a or Me 4b) and for comparison [Zr(η-C 5 H 5 )(η-C 5 H 4 CH 2 Ph)Cl 2 ] 3a were prepared and characterised. The reactions of these compounds with the methide abstracting reagents B(Cwas formed from the reaction of 1b with 0.5 equivalent of B(C 6 F 5 ) 3 . Reaction between 1b and 1 equivalent B(C 6 F 5 ) 3 gave [Me(η-C 5 H 4 CH 2 Ph) 2 Zr(µ-Me)B(C 6 F 5 ) 3 ] 6a and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 21 publications
2
36
1
Order By: Relevance
“…The size and symmetry of substituents linked to the Cp or Ind moieties are essential variables for tuning the polymerization efficiency of catalysts and polymer properties. Benzyl substitution of the ligands is an interesting way to sterically and electronically modify the chemical structure of the catalyst as interactions between a phenyl ring and the transition metal center in metallocenes can occur [5,6]. Computational studies of benzyl-substituted [(g 5 -Cp)(g 5 -CpCH 2 C 6 H 5 )]ZrMe + have shown that g 3 -and g 1 -coordination modes of ring carbons are energetically more favorable than an agostic interaction via hydrogen [7].…”
Section: Introductionmentioning
confidence: 99%
“…The size and symmetry of substituents linked to the Cp or Ind moieties are essential variables for tuning the polymerization efficiency of catalysts and polymer properties. Benzyl substitution of the ligands is an interesting way to sterically and electronically modify the chemical structure of the catalyst as interactions between a phenyl ring and the transition metal center in metallocenes can occur [5,6]. Computational studies of benzyl-substituted [(g 5 -Cp)(g 5 -CpCH 2 C 6 H 5 )]ZrMe + have shown that g 3 -and g 1 -coordination modes of ring carbons are energetically more favorable than an agostic interaction via hydrogen [7].…”
Section: Introductionmentioning
confidence: 99%
“…As expected, the hafnium complex 6 was not active whereas the symmetrical zirconium complex 7 with two more bulky tert -butylsilyl substituted rings showed an activity of 1.4 )/10 6 g PE (mol cat. h) (1 , higher than that found for bulkier substituted rings [6] and similar to that observed for the titanium derivative 4 with only one substituted ring (1.3 )/10 6 g PE (mol cat. h) (1 ).…”
Section: Ethylene Polymerization Studiesmentioning
confidence: 77%
“…We have reported many of these silyl substituted compounds which have been used more recently to stabilize cationic zirconocene species [4] by coordinating the olefinic system of a silyl Á/allyl substituent and to isolate new 'doubly constrained' silyl-h 1 -amido complexes [5]. Formation of cationic zirconocene complexes containing benzyl and the very bulky Si(SiMe 3 ) 3 substituted cyclopentadienyl ligands has been studied and the role of these substituents in ethylene polymerization has been considered [6]. Bulky substituents like tert -butyl groups are responsible for unexpected intramolecular activation processes such as those observed for benzyl and neophyl metallocenes [7] to give metallacyclic derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…ere, the benzyl-moiety is bonded in an η 2 fashion to the zirconium centre and the phenyl moiety is coordinated in the previously described η 1 mode to the metal. [16,17,25] The Zr-C 7 -C 8 -C 9 dihedral angle of 95.5°indicates symmetric coordination, with only a small distortion that is probably caused by the coordinated phenyl moiety. As previously reported, [16,19] the hydrogen attached to the coordinated carbon of the phenyl moiety is bent out of the phenyl plane by 9.62°, away from the zirconium metal.…”
Section: Structural Investigationmentioning
confidence: 99%